Improving Motor Skills in Early Childhood through Goal-Oriented Play Activity - Panggung Sutapa; Kukuh Wahyudin Pratama; Maziah Mat Rosly; Syed Kamaruzaman Syed Ali; Manil Karakauki (MDPI AG, 2021)
Goal-oriented play activity encourages children to exercise and triggers the movement of body muscles. Active muscles are stronger, more agile, faster, and more powerful. Purpose: The purpose of this study is to determine that goal-oriented play activity in early childhood improves motor skills. Methods: Forty children aged 4.5-6 years old were recruited and took part in a set of training activities divided into Posts 1-5. To pass each post, a child had to run, walk on a balance beam, move sticks, throw and catch the ball, and arrange blocks. Training was given three times every week for 12 weeks. Data collected consisted of running 25 m, walking on the balance beam, throwing the ball as far as possible, locomotor movement, arranging cans, and bouncing the ball. Paired t and Wilcoxon signed-rank tests were used for analysis. Results: The results showed that there were significant differences in the motor skills evaluated pre- and post-training with p < 0.05. Conclusion: All six training activities conducted for 12 weeks provided significant improvements in the motor skills areas in children aged 4.5-6 years old.